2020
DOI: 10.21873/anticanres.14358
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome of Mammary Tumors Differs from Normal Mammary Glands But Is Not Altered by Time-restricted Feeding Under Obesogenic Conditions

Abstract: Background/Aim: Time restricted feeding (TRF) mitigates the high-fat diet-enhanced mammary tumorigenesis in a MMTV-PyMT breast cancer model. Materials and Methods: We performed untargeted metabolomic and targeted transcriptomic analyses on mammary tumors from MMTV-PyMT mice fed a standard AIN93G diet, a high-fat diet (HFD), or HFD with TRF (12 h, dark phase) and mammary glands from wild-type mice fed the AIN93G diet. Results: The metabolic profile of mammary tumors differed from that of mammary glands; ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Cholesterol is essential for membrane biogenesis and a precursor for steroid hormone synthesis. Cholesterol is elevated in mammary tumors in MMTV-PyMT mice fed an HFD ( 55 ). Hypercholesterolemia promotes mammary tumorigenesis in MMTV-PyMT mice ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol is essential for membrane biogenesis and a precursor for steroid hormone synthesis. Cholesterol is elevated in mammary tumors in MMTV-PyMT mice fed an HFD ( 55 ). Hypercholesterolemia promotes mammary tumorigenesis in MMTV-PyMT mice ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory rodents are nocturnal animals. They are active in the dark phase of the day (ZT [12][13][14][15][16][17][18][19][20][21][22][23][24]. In a recent transcriptome analysis of liver samples from these pubertal mice, we found that the HFD-fed mice, compared to the AIN93G-fed controls, had greater numbers of differentially expressed genes and KEGG metabolic signaling pathways in the dark phase (particularly ZT [16][17][18][19][20] and fewer numbers in the light phase.…”
Section: Discussionmentioning
confidence: 93%
“…Feeding weanling mice a high-fat diet increases body fat mass, 13 , 14 disrupts the pattern of metabolism (eg, respiratory exchange ratio), 14 and changes plasma concentrations of cytokines that are involved in metabolism (eg, leptin and adiponectin). 13 , 14 Furthermore, the high-fat diet alters metabolic profile of mammary tumors 15 and enhances mammary tumorigenesis 16 in MMTV-PyMT mice. However, there is a lack of knowledge of the impact of dietary fat on pubertal mammary metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…They also observed that TRF decreased the phosphorylation of AKT (also known as PKB, protein kinase B) in tumor tissues, supporting the idea that TRF may be related to autophagy. Yan et al [49–51] also demonstrated that TRF could attenuate the spontaneous metastasis of Lewis lung cancer and reduce the expression of oncogenic genes through a series of animal experiments.…”
Section: Potential Antitumor Effects Of Trementioning
confidence: 99%